Sampling-time harmonic control for cascaded H-bridge converters with thermal control - Marquez, Abraham; Monopoli, Vito Giuseppe; Leon, Jose I.; Ko, Youngjong; Buticchi, Giampaolo; Vazquez, Sergio; Liserre, Marco; Franquelo, Leopoldo G. (2020)
Cascaded H-bridge converter (CHB) is a multilevel topology that is a well-suited solution for multiple applications such as flexible ac transmission systems or motor drives. This paper is focused on a CHB where the cells present an aging mismatch. This can be caused by the maintenance operation which forces the replacement of some damaged cells of the converter with new or repaired ones. In this paper, a new improved approach of the active thermal control (ATC) of the CHB using discontinuous pulsewidth modulation (PWM) (D-PWM) is presented. The D-PWM technique is used to reduce the power losses of one cell reducing its average temperature in order to increase its remaining lifetime. However, the combination of D-PWM with traditional phase-shifted PWM (PS-PWM) introduces high harmonic distortion in the output voltage of the CHB converter at twice the carrier frequency. A detailed harmonic distortion analysis of the CHB output voltage when the D-PWM based ATC is active is presented. From this analysis, a modification of the traditional PS-PWM is derived to eliminate the harmonic distortion at twice the carrier frequency. Experimental results show how the ATC using D-PWM is achieved whereas the harmonic distortion around twice the carrier frequency is eliminated. © 1982-2012 IEEE.